Re-envisioning Women’s Empowerment: A Maqasid Approach to Understanding Women’s Status and Rights in Islam - Basma I. Abdelgafar (17962992) (2023)
Like other human rights treatises, the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) has elicited moral-religious responses from both state and non-state actors, especially in predominantly Muslim societies. The reactions are divided, with supporters and opponents using selective traditional arguments. This paper suggests that the Islamic response lacks a comprehensive approach and is fragmented, relying on partialistic views of the Shariah and offers to adopt a new maqasid methodology (NMM) to examine the status and rights of women in Islam. The paper challenges the focus on inequality as the main cause of injustice and argues that empowering women involves recognizing their relationship with their Creator as well as their relationships to their own selves, other individuals and groups, and all other creatures. The dominance of two policy positions (full acceptance or acceptance with reservations) that assume or neglect these deeper issues is inadequate and does not reflect the potential of an Islamic perspective. The Islamic perspective has yet to be fully explored and cannot endorse positions that view women in conflict with men or that are based on false premises. Other Information Published in: Women's Empowerment and Public Policy in the Arab Gulf States : Exploring Challenges and Opportunities License: http://creativecommons.org/licenses/by/4.0/ See chapter on publisher's website: http://dx.doi.org/10.1007/978-981-99-6006-4_3